Effects of ractopamine HCl dose and treatment period on pig performance in a commercial finishing facility - Main, R.G.; Dritz, Steven S.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; DeRouchey, Joel M. (My University, 2013)
Objective: To evaluate effects of ractopamine HCl (RAC) dose and treatment period on growth performance and carcass composition in a commercial finishing environment. Materials and methods: In Experiment One, a total of 880 pigs (PIC L337 × C22; initially 106.5 ± 0.5 kg) were allotted to four treatments, including doses of 0, 5.0, 7.5, and 10.0 ppm of RAC for 21 days before slaughter. In Experiment Two, 1035 gilts (initially 103.2 ± 0.62 kg) were allotted to nine treatments. Treatments included doses of 5 or 10 ppm RAC for 7, 14, 21, or 28 days before slaughter and a control treatment without RAC. Results: In Experiment One, average daily gain (ADG), gain-to-feed ratio (G:F), and carcass yield increased (linear, P < .05) with increasing dose of RAC. The largest numeric differences were observed as RAC dose increased from 0 to 5 ppm. In Experiment Two, ADG and G:F were greater (P < .05) for pigs fed 5 ppm RAC for 14, 21, or 28 days and for pigs fed 10 ppm for all treatment periods than for control pigs. Carcass yield was greater in pigs fed 10 ppm RAC (P < .05) than in pigs fed 5 ppm RAC or in the controls. RAC dose (5 ppm versus 10 ppm) did not affect carcass lean measures (P > .16). Implications: Feeding RAC at 5 to 10 ppm for 14 to 28 days before slaughter increases ADG, G:F, and carcass yield of pigs reared in a commercial finishing environment.
Keywords: Swine; Ractopamine; Growth